Systems Analysis and Sectoral Linkages Impacting Climate Resilient Development in the SADC Region - Chesterman, Sabrina; Neely, Constance; Gosling, Amanda (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
SADC Future project supplementary material: Systems analysis and sectoral linkages impacting climate resilient development in the SADC region.